2016
DOI: 10.4314/ajtcam.v13i2.25
|View full text |Cite
|
Sign up to set email alerts
|

Acute and sub-chronic oral toxicity studies of methanol extract of <i>Clinacanthus nutans</i> in mice

Abstract: Background: Clinacanthus nutans (C. nutans) Lindau (family Acanthaceae) is a shrub widely cultivated in the South East Asia region, including Malaysia. It has been traditionally used for treatment of various ailments including pain-mediated diseases. Various pharmacological activities of C. nutans have been reported except for its pain-relieving activity. This study was performed to evaluate the acute and sub-chronic oral toxicity of the methanol extract of Clinacanthus nutans (MECN) in male and female mice. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
14
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 20 publications
6
14
4
Order By: Relevance
“…These findings are in agreement with the report of Chavalittumrong et al [58], where a significant decrease body weight of male rats treated with 1.0 g/kg of C. nutans ethanolic extract daily for 90 days compared to the control group was reported. However, it is contrary to the report of Zakaria et al [9], who reported that repeated oral administration of methanolic extract of C. nutans daily for 28 days did not affect the body weight of the mice even at the highest dose of 2500 mg/kg. This perhaps may be due to shorter duration of exposure [56,57] compared to the present study.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…These findings are in agreement with the report of Chavalittumrong et al [58], where a significant decrease body weight of male rats treated with 1.0 g/kg of C. nutans ethanolic extract daily for 90 days compared to the control group was reported. However, it is contrary to the report of Zakaria et al [9], who reported that repeated oral administration of methanolic extract of C. nutans daily for 28 days did not affect the body weight of the mice even at the highest dose of 2500 mg/kg. This perhaps may be due to shorter duration of exposure [56,57] compared to the present study.…”
Section: Discussioncontrasting
confidence: 92%
“…Toxicity evaluation of C. nutans therefore becomes very necessary in order to ascertain its safety levels that should be used for the treatment of various illnesses. The current literature mostly reported the toxicity effects of the aqueous leaf extracts of the plants [11,12], while a few others that employed the methanolic/ethanolic leaf extracts reported that the plant is not associated with toxicity effects mostly based on the evaluation of body weight changes, haematological and serum biochemical parameters [9,13,14], while the effects of the extracts on the histology of liver and kidneys, which were the primary organs involved in the detoxification and excretion of potential toxic substances from the body, were not reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extract (MECN) demonstrated a wide safety margin and is safe for oral consumption up to the dose of 5000 mg/kg while for the chronic oral consumption the dose is up to 2500 mg/kg, all of which did not cause any toxicity, mortality, or body weight changes. From the acute and subchronic toxicities study, the dose range (100, 250, and 500 mg/kg) for antinociceptive study was determined and decided to be 10-, 20-, and 50-fold reduction of the dose used in acute toxicity study (5000 mg/kg) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite all known biological activities in earlier work, empirical evidence that supports its ability to reduce weight and lower blood cholesterol has not been reported. The present study aims to investigate this plant by using doses of methanolic leaf extract of Clinacanthus nutans (MECN) similar to previous research [22,24]. Recent evidence has shown that methanolic leaf extract of Clinacanthus nutans improves lipid profiles in rats [17].…”
Section: Introductionmentioning
confidence: 90%